2015
DOI: 10.3171/2014.10.peds13698
|View full text |Cite
|
Sign up to set email alerts
|

Does the real-time thermal damage estimate allow for estimation of tumor control after MRI-guided laser-induced thermal therapy? Initial experience with recurrent intracranial ependymomas

Abstract: OBJECT Although control of intracranial ependymomas is highly correlated with degree of resection, it is unknown if the same is true for MRI-guided laser-induced thermal therapy (MRgLITT). The authors report their experience with MRgLITT for ependymoma and examine the utility of the real-time thermal damage estimate (TDE), a recent software advance, with respect to completeness of ablation and impact on tumor control. To the authors' knowledge, this is the largest si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 35 publications
(37 reference statements)
1
17
0
Order By: Relevance
“…[ 103 ] Patel et al . [ 108 ] presented their initial experience of MRI-guided LITT for recurrent intracranial ependymomas in 9 ablations for 5 tumors. They reported the possibility of long-term control for these tumors; however, radical ablation is paramount because an incompletely ablated ependymoma will inevitably recur.…”
Section: Laser-induced Thermal Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…[ 103 ] Patel et al . [ 108 ] presented their initial experience of MRI-guided LITT for recurrent intracranial ependymomas in 9 ablations for 5 tumors. They reported the possibility of long-term control for these tumors; however, radical ablation is paramount because an incompletely ablated ependymoma will inevitably recur.…”
Section: Laser-induced Thermal Therapymentioning
confidence: 99%
“…The topics covered include magnetic resonance (MR)-guided percutaneous ablation, anastomosis, therapeutic applications, and diagnostic applications [ Table 2 ]. [ 3 7 11 12 15 17 25 27 33 34 35 38 44 53 61 65 67 74 83 85 92 108 112 113 116 119 120 127 130 131 133 136 137 140 146 147 148 151 ]…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, postoperative MRI showed that ablation lesions were consistent with preoperative planning to within 6 mm. Since then, several groups have used Visualase in the treatment of primary brain tumors (103106), brain metastases, radiation necrosis (104, 107109), spinal metastases (110), and other tumors outside the CNS, most notably prostate cancer (111, 112). NeuroBlate was first trialed in 10 patients with recurrent glioblastoma (90) and has since been used in patients with primary gliomas (89, 113), brain metastases (113, 114), and radiation necrosis (115, 116).…”
Section: Clinical Outcomes Using Commercial Mriglittmentioning
confidence: 99%
“…Furthermore, structures with internal flow, such as vascular and CSF spaces, act as heat sinks and enable focal ablation without damage to adjacent normal brain tissue [4][5][6]. The validity of the Arrhenius model as a reliable predictor of the ablation zone has been established in several studies [7][8][9]. However, the tissue response to ablation can be variable, particularly in heterogenous structures [10,11].…”
Section: Introductionmentioning
confidence: 99%